Results of laboratory studies filtration sandy soils to assess the safe operation of the waterworks sludge storage tanks - Kasperov Георгий; Levkevich Виктор; Pastukhov Сергей; Kukshinov Михаил; Buzuk Александр; Mikanovich Дмитрий; Kobyak Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2015)
Laboratory studies to determine granulometric composition of the soil and chemical analysis of sludge on hydraulic structures of sludge storage tanks «Belaruskali» have been carried out. The average filtration flow and discharge of seepage of soils samples as well as the coefficient of filtration depending on granulometric composition and chemical composition of water has been determined. The processing of experimental data has been performed.